Impact of the first year of COVID-19 vaccination strategy in Brazil - Aguilar, Soraida (2024)
Funding Information: This work is part of the Grand Challenges ICODA pilot initiative, delivered by Health Data Research UK and funded by the Bill & Melinda Gates Foundation and the Minderoo Foundation. This study was also supported by the National Council for Scientific and Technological Development (CNPq), the Coordination for the Improvement of Higher Education Personnel (CAPES) - Finance Code 001, Carlos Chagas Filho Foundation for Research Support of the State of Rio de Janeiro (FAPERJ), the Pontifical Catholic University of Rio de Janeiro. OR is funded by a Sara Borrell grant from the Instituto de Salud Carlos III (CD19/00110). PM acknowledges suppor from the CNPq (Grant 311519/2022-9). OR acknowledges support from the Spanish Ministry of Science and Innovation and State Research Agency through the \u2018Centro de Excelencia Severo Ochoa 2019-2023\u2019 programme (CEX2018-000806-S) and support from the Generalitat de Catalunya through the CERCA programme. All authors carried out the research independently of the funding bodies. The findings and conclusions in this manuscript reflect the opinions of the authors alone. Funding Information: SH and FAB are funded by the CNPq and FAPERJ. PM is funded by CNPq (422470/2021-0) and FAPERJ (E-26/211.645/2021 and E-26/201.348/2022). OR is funded by a Sara Borrell fellowship from the Instituto de Salud Carlos III (CD19/00110), acknowledges support from the Spanish Ministry of Science and Innovation and State Research Agency through the \u2018Centro de Excelencia Severo Ochoa 2019\u20132023\u2019 programme (CEX2018-000806-S), support from the Generalitat de Catalunya through the CERCA programme and received a research grant from the Health Effects Institute for research unrelated to this manuscript. OR was also a member of the Data Safety Monitoring Board in the REVOLUTION and STOP-COVID trials, testing treatments against COVID-19, and is currently a member of the Data Safety Monitoring Board of the RENOVATE trial, testing respiratory support strategies in patients with acute respiratory hypoxaemic failure. Publisher Copyright: © Author(s) (or their employer(s)) 2024. Re-use permitted under CC BY. Published by BMJ.